Evaluation of Dental Diseases in Suffer from Miscellaneous Disorders Domestic Rabbits via Radiographic Imaging and Clinical Examination: A Retrospective Study - Kubra Gerbaga Ozsemir; Murat Karabağlı (Turkish Journal of Agriculture: Food Science and Technology)
In this research, the interpretations of dental disease in domestic rabbits (Oryctolagus cuniculus) suffering from miscellaneous disorders with the use of radiographic anatomical reference lines; additionally, clinical examinations of these cases were presented. The measurements were made on the images of rabbit cranium skull radiographs (n=25). In the examination of incisors, malocclusion (n=19), abnormal prolongation (n=11), penetration of the palatal bone cortex (n=10), and fractures (n=6) were detected. Retrograde elongation in maxillar cheek teeth (n=20), alveolar penetration in mandibular cortex (n=20), root resorption (n=9), and cheek teeth malocclusions (n=20) were detected in the examination of cheek teeth. The most common complaints assigned to the presented patients were diarrhea, mandibular swelling, abnormal elongation of teeth, epiphora, tooth breakage, and loss of appetite. All rabbits suffering from dental disease were also assessed for eye disorders, and tooth-related eye problems were determined in 9 cases. In two cases was more than one problem. Distribution of disease was determined as follows; epiphora (n=6), dacryocystitis (n=2), conjunctivitis (n=2) and exophthalmos (n=1). In addition to a detailed physical examination, radiographic evaluation is important for diagnosis of dental diseases in rabbits. The long mouth cavity with limited opening and similar characteristics of rabbit mouth make it difficult to examine and intervene; in this case, radiographic reference lines offer an important advantage.